The Architecture of the Network of Orchid–Fungus Interactions in Nine Co-occurring Dendrobium Species - Xing, Xiaoke; Liu, Qiang; Gao, Yue; Shao, Shicheng; Guo, Lingling; Jacquemyn, Hans; Zhao, Zeyu; Guo, Shunxing (Frontiers in Ecology and Evolution, 2020)
Orchid-fungus interaction networks often consist of many different fungi that interact with co-occurring orchids in complex ways, but so far it remains largely unclear which processes determine network structure and both ecological and evolutionary mechanisms have been invoked to explain network architecture. In this research, we tested the hypothesis that closely related orchids associate with similar mycorrhizal fungi and vice versa by investigating the architecture of the interaction network between orchid mycorrhizal fungi (OMF) and nine co-occurring epiphytic Dendrobium species. All species grew on the bark of a single tree species (Camelia sinensis) in a traditional tea garden in China, which allowed us to assess the role of evolutionary history in determining the assembly of orchid-fungus communities without the confounding effects of environmental variation. In total, 101 different fungal operational taxonomic units (OTUs) known to be mycorrhizal in orchids were found. Most of the identified mycorrhizal OTUs were members of the Serendipitaceae (80% of all identified mycorrhizal sequences). All orchid species associated with a large number of fungi (average number of links: 31.6 ± 3.8), and orchids from the same species tended to have significantly more similar fungal partners than orchids from different species. The network of interactions was significantly nested (NODF = 41.59, p < 0.01), but not significantly compartmentalized (M = 0.26, Mrandom = 0.27). Phylogenetic analyses showed that the interaction network was not significantly affected by the phylogenies of the orchids or the fungi. Overall, these results indicate that the studied orchid species associated with multiple fungi simultaneously, and that the network of associations was built on asymmetric and weak reciprocal dependences. Associating with multiple fungi may be a successful strategy of orchids to colonize vacant sites and to increase survival of established plants in epiphytic habitats.